Royal Canadian Academy of Arts/Académie royale des arts du Canada : Exhibitions and Members, 1880-1979 - McMann, Evelyn de R. (Evelyn de Rostaing), 1913- (Book collections on Project MUSE., 1981)
This detailed reference work lists, by artists, all works exhibited by the Royal Canadian Academy in its first 100 years. This book draws on many previously unpublished sources, presents an historic view of Canadian art, and greatly enhances a precise knowledge of canadian artists' contributions to our heritage.